Biophysical Studies on Platelet Cofactor I Preparations - Shulman, Sidney; Landaburu, Ricardo H.; Seegers, Walter H. (Thrombosis and Haemostasis, 1960)
Preparations of bovine platelet cofactor I have been examined according to biophysical methods. In the ultracentrifuge the patterns reveal a major component comprising 86% of the total and two faster moving minor components. The sedimentation constants are 6.65, 10.0, and 21.2 Svedberg units. The diffusion constant is 3.30 × 10−7 cm2 sec−1. Associating this value with the main constituent, the molecular weight is found to be 196,000. A molecular axial ratio of 12 is also obtained from these data. An axial ratio of 8 is indicated from viscosity data. The extinction coefficient at 2800 Å is 14.8.